2010
DOI: 10.6028/nist.ir.7744
|View full text |Cite
|
Sign up to set email alerts
|

Improving efficiency of markov chain analysis of complex distributed systems

Abstract: Abstract:In large-scale distributed systems, the interactions of many independent components may lead to emergent global behaviors with unforeseen, often detrimental, outcomes. The increasing importance of distributed systems such as clouds and computing grids will require analytical tools to understand and predict, complex system behavior to ensure system reliability. In previous work, we described how a piecewise homogeneous Discrete Time Markov chain representation of a computing grid can be systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 42 publications
(135 reference statements)
0
14
0
Order By: Relevance
“…The transitions in the cut set can thus be identified as critical transitions, which serve as a basis for describing potential failure scenarios. In previous work [12], we reported the results of experiments which showed that minimal s-t cut set analysis could be used to find all critical state transitions in an absorbing DTMC for a much smaller grid computing system at 1/100 th the computation cost of large-scale simulations. This exhaustive analysis need not be repeated for the problem described in this paper, as there is not the space for it.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The transitions in the cut set can thus be identified as critical transitions, which serve as a basis for describing potential failure scenarios. In previous work [12], we reported the results of experiments which showed that minimal s-t cut set analysis could be used to find all critical state transitions in an absorbing DTMC for a much smaller grid computing system at 1/100 th the computation cost of large-scale simulations. This exhaustive analysis need not be repeated for the problem described in this paper, as there is not the space for it.…”
Section: Discussionmentioning
confidence: 99%
“…These savings increase even more dramatically if combinations of three critical transitions are considered. Though further research is necessary, it is our belief that both in [12] and in this study, we have described an analytical approach that can aid in understanding where and how catastrophic failures may occur in complex systems. The results to date have shown that the approach is tractable for the types of problems we have examined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations